PERAN PEREKAM MEDIS DAN INFORMASI KESEHATAN DALAM PELAKSANAAN VAKSINASI COVID-19 DI RS X - Tania Nirmala; Dina Sonia (Jurnal Kesehatan Tambusai, 2021)
The purpose of this study was to find out the role of Medical Recorders and Health Information in the Implementation of COVID-19 Vaccination at Hospital X. This type of research used a qualitative descriptive method, with a Cross Sectional approach. Data collection techniques using observation, interviews and documentation studies. Vaccination is carried out by health personnel, including medical recorders. Medical recorders has a role that is in accordance with its competence, namely as a data processor, the results of the study show that medical recorders in the implementation of vaccinations are in charge of registering and matching participant data, verifying participant data, recording and reporting service results and in addition to processing medical recorder data, they also carry out other competencies, namely communication. effective. So it can be concluded that in the implementation of this vaccination medical recorders plays a role based on its competence.